Crosstalk between the transcriptional regulation of dopamine D2 and cannabinoid CB1 receptors in schizophrenia: Analyses in patients and in perinatal Δ9-tetrahydrocannabinol-exposed rats. (February 2021) - Di Bartolomeo, Martina; Stark, Tibor; Maurel, Oriana Maria; Iannotti, Fabio Arturo; Kuchar, Martin; Ruda-Kucerova, Jana; Piscitelli, Fabiana; Laudani, Samuele; Pekarik, Vladimir; Salomone, Salvatore; Arosio, Beatrice; Mechoulam, Raphael; et al.
Graphical abstract: Abstract: Perinatal exposure to Δ 9 -tetrahydrocannabinol (THC) affects brain development and might increase the incidence of psychopathology later in life, which seems to be related to a dysregulation of endocannabinoid and/or dopaminergic systems. We here evaluated the transcriptional regulation of the genes encoding for the cannabinoid CB1 receptor ( Cnr1 ) and the dopamine D2 receptor ( Drd2 ) in perinatal THC-(pTHC) exposed male rats, focusing on the role of DNA methylation analyzed by pyrosequencing. Simultaneously, the molecular and behavioral abnormalities at two different time points (i.e., neonatal age and adulthood) and the potential preventive effect of peripubertal treatment with cannabidiol, a non-euphoric component of Cannabis, were assessed. The DRD2 methylation was also evaluated in a cohort of subjects with schizophrenia. We observed an increase in both Cnr1 and Drd2 mRNA levels selectively in the prefrontal cortex of adult pTHC-exposed rats with a consistent reduction in DNA methylation at the Drd2 regulatory region, paralleled by social withdrawal and cognitive impairment which were reversed by cannabidiol treatment. These adult abnormalities were preceded at neonatal age by delayed appearance of neonatal reflexes, higher Drd2 mRNA and lower 2-arachidonoylglycerol (2-AG) brain levels, which persisted till adulthood. Alterations of the epigenetic mark for DRD2 were also found in subjects with schizophrenia. Overall, reported data add further evidence to the dopamine-cannabinoid interaction in terms of DRD2 and CNR1 dysregulation which could be implicated in the pathogenesis of schizophrenia spectrum disorders, suggesting that cannabidiol treatment may normalize pTHC-induced psychopathology by modulating the altered dopaminergic activity.